SEX TANPA NIKAH: Dilema Hukum Positif dan Moralitas Bangsa - Achmad Fageh (Universitas Islam Lamongan, 2019)
Efforts to bring together the synergity of positive legal products and the value of morality of the nation as the wisdom of local cultures to-Indonesiaan needs the seriousness of various parties. Specifically, the provisions of the law governing adultery that truly reflect the aspirations and values that live in the community and are moral mirroring, are indispensable to the attention of many other aspects that Need to also note. While awaiting its realization, the author considers it to be no longer the time when all parties excuse that the freedom and privacy of a person in the sex field is ' closed ' to the law, so that the criminal law stops at the front door of the room. Therefore, maintaining the notion of adultery according to the PENAL code (which is now in force), is the same by validating the sofsion of the values of goodness that live in society. Do we have to be flashed and want to keep that detrimental ' privacy '? Do we still have to ' endure ' by skipping.The formulation of TP fornication in the RUU KUHP has a wider scope than arranged in the KUHP. This is reflected in article 417 and article 419 RUU KUHP, which arranges about the deed of intercourse with a person who is not a husband or his or his/her